Customer-Directed Counterproductive Work Behavior of Gig Workers in Crowdsourced Delivery: A Perspective on Customer Injustice - Yanfeng Liu; Lanhui Cai; Xueqin Wang; Xueli Tan (Systems)
In the platform economy, customers are the primary interaction partners of gig workers, and their behaviors and attitudes significantly influence gig workers’ work experiences and behavioral responses. Based on the stressor–emotion model and social exchange theory, this paper systematically explores the formation mechanism of customer-directed counterproductive work behavior. This study employs structural equation modeling to analyze survey data collected from 385 registered gig workers on crowdsourced delivery platforms in China. The results indicate that customer injustice increases gig workers’ negative emotions, perceived organizational injustice, and customer-directed counterproductive work behavior while decreasing customer commitment. Furthermore, negative emotions, perceived organizational injustice, and customer commitment mediate the relationship between customer injustice and customer-directed counterproductive work behavior. Additionally, job demands act as a buffering mechanism in the occurrence of customer-directed counterproductive work behavior. This study is the first to systematically focus on customer-directed counterproductive work behavior among crowdsourced delivery gig workers, enriching the existing literature. The findings provide practical insights for crowdsourced delivery platforms, aiding in understanding gig workers’ work psychology and optimizing labor management strategies.